2008
DOI: 10.1016/j.sab.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

On-line monitoring of composite nanoparticles synthesized in a pre-industrial laser pyrolysis reactor using Laser-Induced Breakdown Spectroscopy

Abstract: Laser-Induced Breakdown Spectroscopy (LIBS) was employed for on-line and real time process monitoring during nanoparticle production by laser pyrolysis. Laser pyrolysis has proved to be a reliable and versatile method for nanoparticle production. However, an on-line and real time monitoring system could greatly enhance the process optimization and accordingly improve its performances. For this purpose, experiments aiming at demonstrating the feasibility of an on-line monitoring system for silicon carbide nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The investigation of LIBS specifically for the online monitoring of nanoparticle (NP) streams in gas phase was reported by Amodeo et al [179], successfully achieving quantitative analysis of silicon carbide NPs in the size range of 20 to 100 nm. Noll et al reported size-resolved (20 to 800 nm) measurements of ultrafine particulate matter using LIBS for the analysis of calcium chloride particles [180].…”
Section: Application To Nanomaterialsmentioning
confidence: 99%
“…The investigation of LIBS specifically for the online monitoring of nanoparticle (NP) streams in gas phase was reported by Amodeo et al [179], successfully achieving quantitative analysis of silicon carbide NPs in the size range of 20 to 100 nm. Noll et al reported size-resolved (20 to 800 nm) measurements of ultrafine particulate matter using LIBS for the analysis of calcium chloride particles [180].…”
Section: Application To Nanomaterialsmentioning
confidence: 99%
“…23 The experimental parameters were chosen in order to obtain a very fine and uniform particles morphology while reactive gas flows were adjusted to produce stoichiometric powder at a high production rate of about 1 kg/h. In some cases, the sintering additive boron element was introduced during the laser synthesis by adding BCl 3 to the reactant gases to produce composite Si/C/B nano-powders.…”
Section: Powders Synthesis and Characterizationmentioning
confidence: 99%
“…LIBS has already been utilized for on-line monitoring of metal laden aerosols in industrial production, combustion processes [12,13,14], environmental purposes [15,16] and promising results were obtained. More recently, it has been applied to on-line and real time process monitoring during nanoparticle production [17]. LIBS was consequently selected for monitoring purposes near the production processes.…”
Section: Introductionmentioning
confidence: 99%